Pathways at the Iberian crossroads: Dynamic modeling of the middle–upper paleolithic transition - Yaping Shao; Konstantin Klein; Christian Wegener; Gerd-Christian Weniger (PLoS ONE, 2025)
Archaeological and genomic data provide essential yet static insights into human expansion, offering limited understanding of the underlying dynamic processes. As a complementary alternative, we present a high-resolution model of population dynamics and apply it to reconstructing the Middle-to-Upper Paleolithic Transition (MUPT) in Iberia. Through ensemble simulation, we examine Neanderthal (NEA) persistence, modern human (AMH) arrival, and possible interbreeding. The model maps population networks, mobility, and interactions, showing NEAs were confined mainly in coastal refugia and already declining when AMHs arrived. Heinrich Event 5 likely accelerated NEA extinction through climate stress and demographic collapse. AMHs expanded rapidly into Cantabria, overlapping with NEAs and allowing for possibly 2–6% admixture. New dispersal corridors are predicted, showing AMHs moved along the Atlantic coast from southern France into Cantabria, then inland via the Duero Route into Portugal and central Mesetas. By linking climate, demography, and culture, our dynamic model offers a broader explanatory framework that enhances the interpretive power of archaeological and genomic records.